Penerapan Metode Preference Selection Index (PSI) Dalam Pemilihan Anggota Badan Permusyawaratan Desa Kabupaten Bengkulu Selatan - Nanti Kumelasri; Siswanto Siswanto; Eko Suryana (Jurnal Media Infotama, 2023)
Abstract :This thesis is the result of research that describes how much influence the Village Consultative Body has on the people of Tanjung Tebat Village, golden flower District, South Bengkulu Regency. The Village Consultative Body is an institution that embodies democracy in administering village governance. The Village Consultative Council can be considered as the village parliament. As for the background, the writer's interest in writing this thesis is based on the results of observations and initial interviews that the writer conducted at the golden flower sub-district office, where the selection of members of the Village Consultative Council still uses manual assessment or it can be said that it is not efficient. Where the author offers a Preference Selection Index method to be used in selecting the best Village Consultative Body.In the Preferences Selection Index method, the results are obtained by minimal and simple calculations as they are based on statistical concepts without the need for attribute weights. From the calculations, it can be concluded that the best village consultative body members in the golden flower District fall into alternative A5, namely Design Women with a total value of 0.9084 which has been resolved using the Prefence Selection Prefence Selection Index method. Keywords: Election of BPD Members, Method Prefence Selection Index